2019
DOI: 10.1177/0734371x19857799
|View full text |Cite
|
Sign up to set email alerts
|

Is More Commitment Always Better? A Study on the Side Effects of Excessive Organizational Commitment on Work–Family Conflict

Abstract: Despite the growing interest in and efforts for work–family balance, actual improvements in work–family balance have not been that significant in South Korea (e.g., increase in karoshi). This study considers an overly organization-oriented perspective as one of the reasons for this, and focuses on the side effects of excessive organizational commitment (OC) on work–family conflict (WFC), unlike most previous studies focusing on the positive effects of OC. Using the Korean Civil Service Survey, we found that OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 96 publications
1
7
1
Order By: Relevance
“…Surprisingly, organizational commitment has a significant negative effect on reported technical performance, with the highest levels on employees with the lowest performance scores, in opposition to previous studies [ 36 , 37 , 38 ]. It is worth mentioning here that the previous studies were performed in WFO environments and that performance was evaluated globally, with no delimitation between social and technical performance.…”
Section: Discussion and Recommendations For Organizationscontrasting
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, organizational commitment has a significant negative effect on reported technical performance, with the highest levels on employees with the lowest performance scores, in opposition to previous studies [ 36 , 37 , 38 ]. It is worth mentioning here that the previous studies were performed in WFO environments and that performance was evaluated globally, with no delimitation between social and technical performance.…”
Section: Discussion and Recommendations For Organizationscontrasting
confidence: 99%
“…Previous studies have emphasized the positive effects of organizational commitment on job performance [ 36 , 37 , 38 ]. The more committed employees tend to perform well and have a lower tendency to leave their jobs [ 39 ].…”
Section: Literature Review Ad Research Questionsmentioning
confidence: 99%
“…Work occupational commitment was included in this study due to its significance as a predictor for conflict between work and family. Lee and Lee (2021) found that an excessive commitment dedicated to work or the organization would encroach into the family domain, making it more difficult for one to perform in their family role, thus resulting in greater conflict levels. Luk and Shaffer (2005) also reported greater WIF levels for those who committed more time and resources to work.…”
Section: Work Factorsmentioning
confidence: 99%
“…Work and family domains have been the main pillars for most individuals in every society (Ahmad and Skitmore 2003;Lee and Lee 2021). As a result, they may inadvertently serve as the primary source of support or stress in times of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that mental and physical health mediated fully work-to-family conflict while partially mediating work-to-family enrichment (Yucel, 2017). The success of an organization in enhancing job satisfaction correlates significantly with organizational productivity (Lee & Lee, 2019). However, the employee's wellbeing, both married man and woman, can negatively or positively affect job performance and, to some extent, job satisfaction (judge, Bono, Thoresen, & Patton, 2001).…”
Section: Introductionmentioning
confidence: 99%